2020
DOI: 10.1111/1365-2745.13510
|View full text |Cite
|
Sign up to set email alerts
|

Context‐dependent variability in the population prevalence and individual fitness effects of plant–fungal symbiosis

Abstract: Heritable symbionts are often observed at intermediate prevalence within host populations, despite expectations that positive fitness feedbacks should drive beneficial symbionts to fixation. Intermediate prevalence may reflect neutral dynamics of symbionts with weak fitness effects, transient dynamics of symbionts trending towards fixation (or elimination), or a stable intermediate outcome determined by the balance of fitness effects and failed symbiont transmission. Theory suggests that these outcomes should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 96 publications
(130 reference statements)
0
9
0
Order By: Relevance
“…In fact, mutualists often confer benefits in the face of multiple types of stressors. For example, context‐dependent outcomes of fungal endophyte symbiosis in grasses may improve host fitness under drought stress (Afkhami et al, 2014; Donald et al, 2021)—the benefit that expands the distribution of Bromus laevipes by 20%—but also provide protection against biotic stressors such as herbivores (Fuchs & Krauss, 2019), competitors (Vázquez‐de‐Aldana et al, 2013), and pathogens (Pérez et al, 2020). In other systems, different guilds of mutualists may offer benefits to a focal partner along different axes of environmental stress; for example, corals benefit from their symbiotic relationship with photosynthetic algae and can also be defended from herbivores by crustaceans (McKeon et al, 2012).…”
Section: Discussion and Synthesismentioning
confidence: 99%
“…In fact, mutualists often confer benefits in the face of multiple types of stressors. For example, context‐dependent outcomes of fungal endophyte symbiosis in grasses may improve host fitness under drought stress (Afkhami et al, 2014; Donald et al, 2021)—the benefit that expands the distribution of Bromus laevipes by 20%—but also provide protection against biotic stressors such as herbivores (Fuchs & Krauss, 2019), competitors (Vázquez‐de‐Aldana et al, 2013), and pathogens (Pérez et al, 2020). In other systems, different guilds of mutualists may offer benefits to a focal partner along different axes of environmental stress; for example, corals benefit from their symbiotic relationship with photosynthetic algae and can also be defended from herbivores by crustaceans (McKeon et al, 2012).…”
Section: Discussion and Synthesismentioning
confidence: 99%
“…No experiment conducted to evaluate the endophyte effect on plant performance under drought uses plant fecundity or seed production as a response variable of fitness. The consideration of the impact of drought on seed production and the transgenerational consequences for progeny performance becomes especially relevant in species associated with vertically transmitted fungal endophytes, since this not only determines the host fitness but also the microorganism persistence (Gundel et al, 2011 , 2017 ; Cavazos et al, 2018 ; Donald et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this has yielded contrasting results (Semmartin et al, 2015 ; Gundel et al, 2016 ). A recent paper showed that endophyte infection frequency in a population can be highly dynamic, as variation in the environmental context (accounted for interannual variability in precipitation level) may differentially affect any of the underlying processes that determine the symbiosis prevalence, the differential fitness between endophyte-infected and non-infected plants, and the efficiency with which fungal endophytes are transmitted (Donald et al, 2021 ). Particularly in arid environments, survey studies exploring the occurrence of endophyte-infected plants have constantly shown a low incidence of endophyte-symbiotic plants (Novas et al, 2007 ; Gundel et al, 2011 ; Semmartin et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations